2015
DOI: 10.3386/w21655
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Field Choice in College and Graduate School: Determinants and Wage Effects

Abstract: As the workforce has become more educated, educational decisions are no longer just about whether to acquire more, but rather what type of education to pursue. In college, individuals somewhat specialize through their choice of college major. Further specialization occurs in graduate school. This chapter investigates how majors and graduate school affect labor market outcomes as well as how the individuals make these potentially important decisions. To do so, we develop a dynamic model of educational decision-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
182
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(192 citation statements)
references
References 74 publications
(138 reference statements)
5
182
0
5
Order By: Relevance
“…While economically significant, it is interesting to note that this estimate is lower than most of the science major premia which have been obtained in earlier studies, including those based on structural models of college major choice (Altonji, Arcidiacono & Maurel 2016). This finding may partly reflect the fact that our estimates control for selection on ability using a choice model that is more flexible in what is included in the individual's information set.…”
Section: Wage Parametersmentioning
confidence: 56%
“…While economically significant, it is interesting to note that this estimate is lower than most of the science major premia which have been obtained in earlier studies, including those based on structural models of college major choice (Altonji, Arcidiacono & Maurel 2016). This finding may partly reflect the fact that our estimates control for selection on ability using a choice model that is more flexible in what is included in the individual's information set.…”
Section: Wage Parametersmentioning
confidence: 56%
“…3 Altonji (1993) and Arcidiacono (2004) are notable exceptions, who incorporate the notion of uncertainty about ability into the probability of completing a college major in order to distinguish between ex ante and ex post returns to a particular course of study. See also the recent survey by Altonji, Arcidiacono, and Maurel (2016). 4 For example, it has been suggested that some managers, including CEOs, have more faith in their firm or in those that they acquire than is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Major choice has a causal effect on future earnings (e.g. Altonji, Arcidiacono and Maurel, 2016;Kirkeboen, Leuven and Mogstad, 2016) and between 10 and 50 percent of the gender wage gap can be explained by gender differences in major choice (Brown and Corcoran, 1997;Daymont and Andrisa, 1984;Gerhart 1990;Machin and Buhani, 2003).…”
Section: Introductionmentioning
confidence: 99%